2021
DOI: 10.1002/ajh.26194
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and safety of anticoagulants for the treatment of heparin‐induced thrombocytopenia

Abstract: Background The effectiveness and safety of non‐heparin anticoagulants for the treatment of heparin‐induced thrombocytopenia (HIT) are not fully established, and the optimal treatment strategy is unknown. In a systematic review and meta‐analysis, we aimed to determine precise rates of platelet recovery, new or progressive thromboembolism (TE), major bleeding, and death for all non‐heparin anticoagulants and to study potential sources of variability. Methods Following a detailed protocol (PROSPERO: CRD4202021902… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 103 publications
0
29
0
Order By: Relevance
“…In a recent meta-analysis, the application of argatroban appeared to associate with the lowest rates of thromboembolic events and of bleeding complications, on top of a shorter hospitalization length [ 87 ]. A systematic review concluded a similarity in the efficacy and safety of fondaparinux (heparin-derivative), bivalirudin or danaparoid [ 88 ].…”
Section: Platelets In Heparin-induced Thrombocytopenia (Hit)mentioning
confidence: 99%
“…In a recent meta-analysis, the application of argatroban appeared to associate with the lowest rates of thromboembolic events and of bleeding complications, on top of a shorter hospitalization length [ 87 ]. A systematic review concluded a similarity in the efficacy and safety of fondaparinux (heparin-derivative), bivalirudin or danaparoid [ 88 ].…”
Section: Platelets In Heparin-induced Thrombocytopenia (Hit)mentioning
confidence: 99%
“…a lack of adequate randomised controlled trials. [37] The choice of alternative anticoagulant will depend on clinician experience, drug availability, cost, expected drug-drug interactions, availability of laboratory testing for drug monitoring, patient age, organ function, weight, comorbidities and bleeding risk, as well as other established factors. [21] For most clinically stable patients without an excessive bleeding risk, fondaparinux or direct oral anticoagulants (DOACs) such as rivaroxaban are reasonable choices for the initial treatment of acute HIT.…”
Section: In Practicementioning
confidence: 99%
“…Numerous case reports, case series, and observational studies describing the use of DOACs in HIT have been published [ 34 , 35 , 36 ], but there remains a lack of high-quality randomized clinical trials (RCT) evaluating the efficacy and safety of DOACs in HIT patients. In the recently published systematic review and meta-analysis of 92 studies reporting clinical outcomes of patients treated with non-heparin anticoagulants (argatroban, danaparoid, fondaparinux, DOACs, bivalirudin, and other hirudins) for acute HIT, Nilius et al [ 37 ] outlined significant bias in some studies linked to the lack of information about patient treatment, adherence to anticoagulant therapy, the lack of appropriate control groups, and the brief follow-up period. The rate of platelet recovery, risk of new or progressive thromboembolism, or occurrence of major bleeding complications were nonetheless not affected by patient populations (isolated HIT patients vs. HITT patients vs. all HIT and HITT patients), diagnostic testing strategy (PF4/H immunoassays vs. clinical criteria vs. SRA/HIPA), or study design (prospective study vs. RCT vs. retrospective study) which means that this study provides the best level of evidence available, according to the authors.…”
Section: Hit: Update On Doacs Usementioning
confidence: 99%
“…They reported a platelet count recovery (i.e., ≥150 G/L) in 96% (CI95%: 88–99%) of HIT patients treated with DOACs ( n = 74), where no significant difference with argatroban, danaparoid, or fondaparinux was noticed. Only bivalirudin was associated with a significant decreased rate of platelet count recovery (74%, CI95%: 58–85%) [ 37 ]. In 2019, Barlow et al [ 38 ] published an exhaustive compilation of literature data regarding the use of DOACs in HIT, where they regrouped biological and clinical features of 104 patients with probable HIT who were treated with DOACs.…”
Section: Hit: Update On Doacs Usementioning
confidence: 99%